2008
DOI: 10.1038/nn.2236
|View full text |Cite
|
Sign up to set email alerts
|

Transient neurites of retinal horizontal cells exhibit columnar tiling via homotypic interactions

Abstract: Sensory neurons with common function are often non-randomly arranged and form dendritic territories that exhibit little overlap or tiling. Repulsive homotypic interactions underlie such patterns in cell organization in invertebrate neurons. In mammalian retinal horizontal cells, however, it is unclear how dendro-dendritic repulsive interactions can produce a non-random distribution of cells and their spatial territories because mature horizontal cell dendrites overlap substantially. By imaging developing mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
119
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 47 publications
9
119
0
Order By: Relevance
“…Upon analyzing late embryonic retinae, before HCs have completed their migration to the OPL, one or two apical and basal processes were observed that extended from the somata of GFP + HCs as they migrated radially towards their prospective layer. Also, tangential HC movements, in which somata squeezed through thick, lateral neurites, were seen near the level of the eventual HC layer, confirming the interpretation of previous results from clonal analyses that proposed that discrete cells located outside of their clonal columns must have moved tangentially (see also Cook and Chalupa, 2000).At early postnatal stages, as the HCs settle into their prospective stratum, the vertical neurites were observed to become more numerous and branched, while also exhibiting dynamic extension and retraction every one to two hours (Huckfeldt et al, 2009). Unexpectedly, these radially oriented neurites were confined to distinct columnar territories, and neurites from adjacent cells appeared to be in close physical contact, but displayed minimal overlap (Huckfeldt et al, 2009).…”
supporting
confidence: 87%
See 4 more Smart Citations
“…Upon analyzing late embryonic retinae, before HCs have completed their migration to the OPL, one or two apical and basal processes were observed that extended from the somata of GFP + HCs as they migrated radially towards their prospective layer. Also, tangential HC movements, in which somata squeezed through thick, lateral neurites, were seen near the level of the eventual HC layer, confirming the interpretation of previous results from clonal analyses that proposed that discrete cells located outside of their clonal columns must have moved tangentially (see also Cook and Chalupa, 2000).At early postnatal stages, as the HCs settle into their prospective stratum, the vertical neurites were observed to become more numerous and branched, while also exhibiting dynamic extension and retraction every one to two hours (Huckfeldt et al, 2009). Unexpectedly, these radially oriented neurites were confined to distinct columnar territories, and neurites from adjacent cells appeared to be in close physical contact, but displayed minimal overlap (Huckfeldt et al, 2009).…”
supporting
confidence: 87%
“…Unexpectedly, these radially oriented neurites were confined to distinct columnar territories, and neurites from adjacent cells appeared to be in close physical contact, but displayed minimal overlap (Huckfeldt et al, 2009). These non-overlapping neuritic domains also coincided with an increase in intercellular spacing between neighboring HCs, suggesting that transient vertical neurites, rather than lateral dendro-dendritic contacts, participate in the homotypic repulsive interactions that drive mosaic formation (Fig.…”
Section: Hcs Employ a Novel Methods Of Mosaic Formationmentioning
confidence: 98%
See 3 more Smart Citations